Energy storage onboard zero-emission two-wheelers : challenges and technical solutions - Van Ga Bui; Thi Minh Tu Bui; Anh Tuan Hoang; Sandro Nižetić; R. Sakthivel; Van Nam Tran; Van Hung Bui; Dirk Engel; Hadiyanto Hadiyanto (Sustainable energy technologies and assessments, 2021)
The two-wheelers powered by battery, hydrogen fuel cell, or a combination of these two power sources are the potential candidates for the greenhouse gas emission reduction strategy in the future although they have been running into difficulties relating to the onboard energy storage technology. Therefore, the main aim of this review paper is to present the existing challenges and technical solutions to the energy storage of two-wheelers. Indeed, exchanging batteries and swapping metal hydrides hydrogen storage canisters were found to be the appropriate solutions, in which fuel cell and the metal hydride canister could constitute a cogeneration system that the heat needed for hydrogen desorption from the metal hydride canister could be recycled from the waste heat of fuel cell stacks or stored in phase change material during the uptake process. Furthermore, powertrain layouts of the fuel cell two-wheelers and the fuel cell-battery hybrid two-wheelers based on the traditional two-wheeler platforms were also suggested in this paper. More importantly, a novel concept associated with the “zero-emission two-wheeler-building” polygeneration system was also suggested to improve the global energy conversion efficiency. Finally, the energy system of two-wheelers powered by battery, fuel cell, and fuel cell-battery hybrid was thoroughly analyzed and compared.